Disharmony and Struggle: Management and Mobilization of Digital-Based Economic Resources in Tourist Village - Purnamawati, I Gusti Ayu; Yuniarta, Gede Adi; Nugraha, I Gusti Bagus Baskara; Dautrey, Jean Marc (Universitas Brawijaya, Indonesia, 2024)
The development of digital platforms has not fully reached tourist villages optimally, apart from the fact that their management still contains conflicts of interest between stakeholders. This research examines the role of community empowerment, implementation of sustainable village development programs, and implementation of digital platforms on the management and mobilization of economic resources. The research type is quantitative and the population consists of 8.402 people in Sudaji tourist village, Buleleng-Bali. A total of 110 people were used as samples (village heads, pokdarwis, traditional kelian, and the community) with a random sampling technique using the Slovin formula. Data collection uses a questionnaire with a Likert scale. The results show that the community empowerment variable does not affect the mobilization of economic resources. In contrast, the sustainable development variable shows different results where it significantly positively impacts the mobilization of economic resources. Finally, the digital platform implementation variable does not affect the mobilization of economic resources. This research focuses on the interests of the community as stakeholders so that they can access economic resources optimally and have an impact so that they can empower them with their capacity to increase economic independence while meeting their basic needs so that they become resource literate with the digital world and sustainable villages can be realized.